Jaringan neural Untuk Pengenalan Pola yang Invarian Terhadap Translasi Dan Rotan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
Analog coupled neurons (CN) can be used in trainable pattern recognition systems. A training algorithm called Coupled Neuron Rule (CNR) is used to implement classification functions. A character recognition.system involving an invariance network and a trainable classifier is proposed. The invariance net can be trained to produce a set of outputs that are insensitive to translation and rotation of the retinal input patterns. The outputs of the invariance net are scrambled. When these outputs are fed to a trainable classifier, the final outputs are descrambled and the original patterns are reproduced in standard position and orientation